2020
DOI: 10.21037/atm-20-5460
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin alleviates denervation-induced muscle atrophy via regulating the Sirt1/PGC-1α axis and STAT3 signaling

Abstract: Background: Our prior studies have shown that inflammation may play an important triggering role during the process of denervated muscle atrophy. The nonsteroidal anti-inflammatory drug aspirin exhibits the effect of anti-inflammatory factors. This study will investigate the protective effect of aspirin on denervated muscle atrophy and the underlying mechanism.Methods: Mouse models of denervated muscle atrophy were established. The protective effect of aspirin (20 mg/kg/d, i.p.) on denervated muscle atrophy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Our study showed that ubiquitin-proteasome system and autophagy lysosomal system are activated in the process of denervationinduced muscle atrophy, but the trigger factors that initiate their activation are not yet clear. Our previous studies suggested that oxidative stress and inflammation may be the trigger factors for activation of the ubiquitin-proteasome and autophagy lysosomal systems (6,18,31). Further studies are needed to confirm the possible molecular mechanism.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our study showed that ubiquitin-proteasome system and autophagy lysosomal system are activated in the process of denervationinduced muscle atrophy, but the trigger factors that initiate their activation are not yet clear. Our previous studies suggested that oxidative stress and inflammation may be the trigger factors for activation of the ubiquitin-proteasome and autophagy lysosomal systems (6,18,31). Further studies are needed to confirm the possible molecular mechanism.…”
Section: Discussionmentioning
confidence: 95%
“…Low nutrients, disuse, systemic inflammation, unloading, chronic kidney disease (CKD), cancer, or ageing provoke a catabolic state characterized by enhanced muscle proteolysis (25,26). Our previous study also found that the expression of Atrogin-1 and MuRF-1 was significantly increased in denervated skeletal muscle, which played an important role in the degradation of muscle protein (11,14,18). The sequencing results of this study found that ubiquitin-conjugating enzyme E2O (UBE2O), WW domain containing E3 ubiquitin protein ligase 2 (WWP2), thyroid hormone receptor interactor 12 (TRIP12), HECT and RLD domain containing E3 ubiquitin protein ligase 3/4 (HERC3/4), ubiquitin-conjugating enzyme 7-interacting protein 5 (UIP5), MDM2 protooncogene (Mdm2), midline 1 (MID1), and tripartite motifcontaining 37 (Trim37) were up-regulated in denervated skeletal muscles, which confirmed the important role of ubiquitin-mediated proteolysis in the process of denervationinduced muscle atrophy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aging is associated with both neuromuscular denervation and reduced physical activity. Since it is known that denervation [ 124 , 126 , 131 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ] and muscle disuse [ 214 , 215 , 216 ] independently impact mitophagic pathways, work is required to determine the independent nature of these stimuli on mitophagy. Furthermore, acute endurance exercise acts as a stimulus that promotes mitophagy in young muscle, used to prune the mitochondrial pool and create a healthier tissue [ 13 ].…”
Section: Regulation Of Mitophagy In Musclementioning
confidence: 99%
“…The cause of the atrophic phenotype is the imbalance of protein metabolism, that is, protein synthesis is inhibited and protein degradation is activated (8). Three major protein degradation pathways are activated during muscle atrophy as follows: the ubiquitin-proteasome pathway, autophagylysosome pathway, and calpain pathway (9)(10)(11). Two studies using proteomics in denervated muscle atrophy model found that a large number of protein expression changes were accompanied by muscle atrophy, ubiquitin proteasome pathway was widely activated (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%